Mineralocorticoid Receptor Antagonists in Diabetic Kidney Disease - Kawanami, Daiji; Takashi, Yuichi; Muta, Yoshimi; Oda, Naoki; Nagata, Dai; Takahashi, Hiroyuki; Tanabe, Makito (Frontiers in Pharmacology, 2021)
Diabetic kidney disease (DKD) is a major cause of end-stage kidney disease (ESKD) worldwide. Mineralocorticoid receptor (MR) plays an important role in the development of DKD. A series of preclinical studies revealed that MR is overactivated under diabetic conditions, resulting in promoting inflammatory and fibrotic process in the kidney. Clinical studies demonstrated the usefulness of MR antagonists (MRAs), such as spironolactone and eplerenone, on DKD. However, concerns regarding their selectivity for MR and hyperkalemia have remained for these steroidal MRAs. Recently, nonsteroidal MRAs, including finerenone, have been developed. These agents are highly selective and have potent anti-inflammatory and anti-fibrotic properties with a low risk of hyperkalemia. We herein review the current knowledge and future perspectives of MRAs in DKD treatment.